2006
DOI: 10.1177/1469787406069055
|View full text |Cite
|
Sign up to set email alerts
|

Teaching style and learning in a quantitative classroom

Abstract: Education research over the last few decades has focused on the debate over which classroom pedagogies best encourage learning: teacher-centred or student-centred. Although research appears to support the philosophy that student-centred teaching provides for better learning, the supporting research is frequently limited to observational studies or limited in experimental design. Despite this, the trend has been to encourage teachers to adopt a more student-centred approach both in the teaching of the course ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0
4

Year Published

2009
2009
2019
2019

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 1 publication
0
18
0
4
Order By: Relevance
“…A study of teacher-centred versus student-centred teaching styles and learning modes in an introductory university statistics course revealed that the teacher-centred class was significantly higher rated on achievements in a quantitative classroom (Giles et al, 2006). Statistics and economics are closely related and, hence, understanding of the effect of teaching style in a quantitative classroom should have much in common.…”
Section: Discussionmentioning
confidence: 99%
“…A study of teacher-centred versus student-centred teaching styles and learning modes in an introductory university statistics course revealed that the teacher-centred class was significantly higher rated on achievements in a quantitative classroom (Giles et al, 2006). Statistics and economics are closely related and, hence, understanding of the effect of teaching style in a quantitative classroom should have much in common.…”
Section: Discussionmentioning
confidence: 99%
“…En este trabajo se ha adoptado la segunda postura, de allí que se consideren, desde un punto de vista descriptivo, distintos factores extrínsecos (actividad profesional, disciplina de enseñanza, contexto institucional) e intrínsecos (edad, sexo, formación pedagógica, experiencia docente) en relación con la adopción de los diversos estilos de enseñanza en la muestra estudiada. Algunos autores (Giles, Ryan, Belliveau, De Freitas y Casey, 2006) afirman que la investigación sobre la educación de las últimas décadas se ha centrado en el debate acerca de la orientación pedagógica -centrada en el profesor o centrada en el estudiante-que promueve mejores aprendizajes. Aunque la investigación parece apoyar la filosofía de que la enseñanza centrada en el estudiante brinda un mejor aprendizaje, la naturaleza de corto plazo de la mayoría de los estudios parece favorecer una clase centrada en el profesor, ya que es la norma en universidades, dado que, al parecer, los estudiantes se sienten más cómodos con ese enfoque.…”
Section: Conclusionesunclassified
“…Asimismo, entre los aspectos más valorados en las prácticas educativas que favorecen un aprendizaje eficaz algunos estudios señalan la preocupación por los estudiantes, la calidad de las relaciones educativas (Giles, Ryan, Belliveau, De Freitas & Casey, 2006) y la atención de las necesidades particulares de los estudiantes (Mendes, 2003).…”
Section: Evaluación De Estilos De Enseñanza En La Universidadunclassified
“…To assess the attitudes and predict the ability for change and to establish appropriate techniques for valid and reliable measurements are needed primarily. Also, among the most valued aspects of educational practices that promote effective learning, some studies point: concern for students, quality of educational relationships (Giles, Ryan Belliveau, De Freitas, & Casey, 2006) and attention to the particular needs of students (Mendes, 2003). From the identification of learning styles, we can generate changes in those approaches that promote effective teaching.…”
Section: Introductionmentioning
confidence: 99%